2017
DOI: 10.1017/s0142716417000467
|View full text |Cite
|
Sign up to set email alerts
|

Morphological awareness and visual processing of derivational morphology in high-functioning adults with dyslexia: An avenue to compensation?

Abstract: This study examined the processing of derivational morphology and its association with measures of morphological awareness and literacy outcomes in 30 Dutch-speaking high-functioning dyslexics, and 30 controls, matched for age and reading comprehension. A masked priming experiment was conducted where the semantic overlap between morphologically related pairs was manipulated as part of a lexical decision task. Measures of morphological awareness were assessed using a specifically designed sentence completion ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 59 publications
3
32
0
Order By: Relevance
“…Although phonological deficits have been demonstrated to account for a significant portion of the variance in reading by dyslexics, a significant portion of the variance remains unexplained. To account for this remaining variance recent studies have begun to explore alternative cognitive variables which may contribute for the literacy difficulties of individuals with dyslexia; such as orthographic processing (Ziegler et al, 2010 ; Boros et al, 2016 ) morphological awareness (Law et al, 2015 , 2018 ; Cavalli et al, 2017 ) or statistical learning (Krishnan et al, 2016 ; Schmalz et al, 2017 , Vandermosten et al, 2018 ). An additional factor that has been proposed to act as a critical bridge between the previously identified cognitive and behavioral deficits of individuals with dyslexia lays within the formation and integration of grapheme-phoneme mappings.…”
Section: Introductionmentioning
confidence: 99%
“…Although phonological deficits have been demonstrated to account for a significant portion of the variance in reading by dyslexics, a significant portion of the variance remains unexplained. To account for this remaining variance recent studies have begun to explore alternative cognitive variables which may contribute for the literacy difficulties of individuals with dyslexia; such as orthographic processing (Ziegler et al, 2010 ; Boros et al, 2016 ) morphological awareness (Law et al, 2015 , 2018 ; Cavalli et al, 2017 ) or statistical learning (Krishnan et al, 2016 ; Schmalz et al, 2017 , Vandermosten et al, 2018 ). An additional factor that has been proposed to act as a critical bridge between the previously identified cognitive and behavioral deficits of individuals with dyslexia lays within the formation and integration of grapheme-phoneme mappings.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, among the 80 words with affixes prepared, 22 of them were misread. Law, et al (2017) argued that a hierarchical structure of linguistic units is employed during early visual word processing in which the processing of smaller linguistic units is required to process larger-size units. He argued that such situation would ultimately limit the visual processing of morphemes, thus limiting the morphological process.…”
Section: The Frequency Of Morphological Deviationsmentioning
confidence: 99%
“…This implied that adolescent dyslexic readers may have difficulties in complex words which have affixes in it. Previous studies suggested that morphological awareness is related to word recognition (Kieffer, 2014;Cavalli, et al, 2017;Law, et al, 2017). Therefore, lacking morphological awareness might cause delayed ability in recognising words which reflected in their struggle, errors, or difficulties in reading.…”
Section: The Types Of Morphological Processes That Occurred In the Deviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this common learning disability involves about 80 percent of the learning disabled population, although the prevalence rate may differ from country to country [16]. Many researchers report that dyslexia is created by four causes: perceptual deficits [17][18][19][20][21], memory deficits [22,23], language processing deficits [7], and visual processing deficits [24][25][26]. Dyslexia does not only affect reading and writing but it has also been proved to cause topographic disorders and orientation problems [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%